Stable metal–organic frameworks with low water affinity built from methyl-siloxane linkers. Issue 57 (11th June 2020) - Delmas, Luke C.; White, Andrew J. P.; Pugh, David; Evans, Arwyn; Isbell, Mark Antonin; Heng, Jerry Y. Y.; Lickiss, Paul D.; Davies, Robert P.
Abstract : A new approach to the development of MOF materials with low water affinity is presented using siloxane-derived linkers. The low water affinity is conferred by the linker without the requirement of any post-synthetic processing apart from activation. Abstract : A tetracarboxylic acid with a methyl-substituted siloxane core (L -H4 ) has been prepared and applied in the construction of water stable MOFs with low water affinity. L -H4 itself crystallizes as an interpenetrated 3D hydrogen-bonded network. Reaction of L -H4 with Zr IV /Hf IV gave IMP-32-Zr/Hf – both 3D MOFs of scu topology.